Anatomi Daun Kacang Hijau Genotipe Toleran dan Sensitif Naungan - Sundari, Titik; Soemartono, ,; Tohari, ,; Mangoendidjojo, W. (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The research to study the leaf anatomy of tolerant and sensitive mungbean genotypes to shading was conducted at Research Station of the Indonesian Legume and Tuber Crops Research Institute (ILETRI) from September to December 2004. Nine tolerant genotypes to shading including MMC 87 D-KP-2, MLG 369, MLG 310, MLG 424, MLG 336, MLG 428, MLG 237, MLG 429 and VC2768B and three sensitive genotypes including Nuri, MLG 460 and MLG 330 were tested in two shading levels, i.e., 0% (control) and 52% using randomized complete block design with three replications. The results showed that the leaves of tolerant genotypes have fewer thrichomes, thicker leaves, thinner epidermis cells, longer palisade tissues and greater number of stomata than those of sensitive genotypes when planted under shading condition. Key words: Mungbean, leaf anatomy, tolerant, sensitive, shading